Ablation behaviors of ZrC-TiC coatings prepared by vacuum plasma spray: Above 2000 °C. Issue 11 (September 2019) - Pan, Xiaohui; Niu, Yaran; Liu, Tao; Zhong, Xin; Li, Chong; Shi, Minhao; Zheng, Xuebin; Ding, Chuanxian
Abstract: ZrC-TiC coatings were fabricated by vacuum plasma spray and their ablation resistance were evaluated and compared with ZrC-SiC coating by a plasma flame with a heat flux of 4.02 MW/m 2 . The microstructure and phase compositions of the as-sprayed and ablated coatings were characterized and the function of TiC addition on the ablation resistance was investigated. The results showed that the ablation resistance of the ZrC-TiC coating was much better than that of the ZrC-SiC coating under the present ablation conditions. The decrease of surface temperatures with the increasing of TiC content were observed. (Zr, Ti)O2 eutectic phase in liquid state was observed. The low vapor and decomposition pressures of TiO2, combined with the formation of (Zr, Ti)O2 liquid contributed to the excellent ablation resistance of the ZrC-TiC coating. This work affirmed that TiC could be an ideal addition to improve the ablation resistance of the ZrC coating in harsh environment above 2000 °C.